Drivers of exceptional job creation : a dynamic probit approach using portuguese firm-level data - Rodrigues, Francisco (2022)
It is a well-established fact that a small number of firms, known as Gazelles, drive a disproportionately large amount of net job creation. This fact has attracted considerable attention from researchers, who have been focusing on trying to understand what differentiates this type of firms from their slow-growth peers. In this paper, we expand the ongoing survey on Gazelles by focusing on the Portuguese case. Particularly, we examine how is high-growth associated with the firms´ age, access to equity and external finance and the workforce human capital. We also test whether high-growth is linked with the firms´ ability to export and innovate through R&D. In this paper, we also explore whether high-growth episodes display some form of state dependency by adding a dynamic component in the form of the lagged value of the Gazelle status. As for results, we find no supporting evidence in favour of persistency, as past growth events are negatively associated with current growth. This is in line with the recent literature on the topic that points to the lack of persistence in the growth process as a consistent enough result worth of being considered as a stylized fact about Gazelles. Nevertheless, we do find that younger firms are more likely to grow at the fastest pace and that human capital is an important determinant for high-growth. Results also point to the fact that fast-growing firms were not hampered by lack of access to adequate external funding during the period, and that they relied primarily on equity to finance their growing needs. Moreover, we find that, once firms’ experience in the market is considered, being an exporter is a relevant factor when it comes to high-growth events. Similarly, the innovative capacity of firms seems to be crucial in outstanding job creation episodes. Finally, our results suggest that it is an enhanced innovative capacity, the availability of equity, as well as the ability of experienced firms to export that might set the difference between the average growth performance and the exceptional growth performance, pointing to nonlinearities in the growth process of firms.